Ethnobotanical use and diversity of Medicinal plants in Zana and Laelay Koraro woredas, Ethiopia - Tewelde, Fitsumbirhan (The Indonesian Forestry Certification Cooperation, 2025)
A study on the diversity and ethnobotanical uses of medicinal plants was conducted in Zana and Laelay Koraro Woredas, in Northwestern Tigray, Ethiopia, in December 2023. The study used ethnobotanical techniques like informant consensus, field observations, semi-structured interviews, ranking and both purposive and stratified sampling methods. In both woredas, a total of 117 medicinal plant species were identified, representing 53 families and 93 genera. The Fabaceae (11.11%), Solanaceae (6.8%), and Euphorbiaceae (4.3%) families were the most commonly used medicinal plants. The most prevalent growth forms were shrubs (35%), trees (33%), and herbs (26%). With 37.6% of the plant, leaves were the most commonly used part, followed by roots (22.8%) and seeds (8.7%). Internal application accounted for 61% of herbal preparations, with 39% of the remainder being used externally. Acaia Lehai is the most endangered medicinal plant, primarily due to agricultural expansion. Lepidium sativum is the preferred remedy for treating febrile illnesses. The study revealed a strong and significant positive correlation between the age of healers and their familiarity with medicinal plants (p < 0.01, r = 0.7) and a weak negative correlation between knowledge of these plants and educational attainment. According to the study, the availability of plant-based medications and their link to medical knowledge have been crucial in maintaining a wide variety of medicinal plant species. Patchy forests are essential hotspots for these plants, providing important information for pharmacological and phytochemical research as well as useful resources for healers. To promote conservation and sustainable forest management, it is essential to ensure that future generations respect and continue to utilize traditional medicine. Educating the use of medicinal plants and how local elders treated for youths are fundamental for the development of modern medicine and pharmacological results.